(untitled) - Holmes, Stewart W. (Rutland, 1973)
The book is divided into fifteen chapters, each devoted to a central tenet of Zen Buddhism, which is then elaborated upon through the presentation of several Chinese or Japanese paintings and a number of haiku, all of which are masterfully related to the tenet through a simple prose explantion. The tone is often light and playful, but the insights are profound, and the various parts of the book flow together flawlessly.
Keywords: Sumie,Painting, zen,Haiku